1983
DOI: 10.1152/ajpendo.1983.244.5.e431
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin in liver tissue extracts and in liver perfusates from hypoxic rats

Abstract: An attempt to evaluate the role of the liver in extrarenal erythropoietin production was made by measuring the content of erythropoietin in homogenates and perfusates from hypoxic rat livers. Extracts from livers from nephric or anephric animals rendered both anemic and hypoxic showed no detectable erythropoietin despite the fact that both plasma and kidney extracts contained large amounts of erythropoietin. This lack of measurable erythropoietin in the liver is not caused by degradation of erythropoietin duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…In CRF, the adaptation of EPO levels to Hb concentration is lost, EPO production is seriously disturbed and its levels are much lower than those observed in non-renal anaemias of Assessment of Erythropoietin Levels and Some Iron Indices in Chronic Renal Failure and Liver Cirrhosis Patients comparable severity. Hepatically produced EPO is evidently of no compensatory value [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In CRF, the adaptation of EPO levels to Hb concentration is lost, EPO production is seriously disturbed and its levels are much lower than those observed in non-renal anaemias of Assessment of Erythropoietin Levels and Some Iron Indices in Chronic Renal Failure and Liver Cirrhosis Patients comparable severity. Hepatically produced EPO is evidently of no compensatory value [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In hypoxic animals, EP can be extracted from renal tissues but not other tissues (2, 3). The only other organ which has been implicated in EP production is the liver of fetal (14) or nephrectomized (1,3,8) animals. The recent cloning of the mouse EP gene (12) provides the probes necessary for analysis of the organ distribution, quantitation, and time course of accumulation of EP-specific mRNA transcripts in mice made hypoxic by blood loss.…”
mentioning
confidence: 99%
“…In the Erslev lab, Zon dissected rat livers in search of erythropoietin, hoping to shed light on how the hormone was made and could be produced for medical use. He concluded that the livers contained low amounts of erythropoietin ( 4 ), but his fascination surrounding blood cells and anemia endured. Erslev advised Zon to continue training in hematology at Harvard University.…”
Section: Hooked By a Lecturementioning
confidence: 99%